INOVASI KAYU GELAM SEBAGAI KEARIFAN LOKAL UNTUK ESTETIKA RUMAH MURAH BAGI SEKTOR INFORMAL DI PALEMBANG (Talenta Publisher, 2018)
All this time Kayu Gelam more used as complementary construction material (kayu racuk) than as main construction or architectural material. Live in wet area like swamps or turf area with 5-10 years sow period, this Kayu Gelam could undertake relative extended time: 10 years or more in changing mediumâ€”like land, and up to 40 years in submerged condition.This very entitled â€œInnovation of Kayu Gelam as Local Wise to Aesthetic of Low-Waged House for Informal Sector at Palembangâ€ researchâ€™s purpose is to give society alternative utilization of Kayu Gelam as main construction and architectural faÃ§ade.Alongside architectural faÃ§ade that based on Local Wise, Kayu Gelam is also giving more competitive trade value than government could offer. Society that is not facilitated by banking service could build this Kayu Gelam house by self-supporting action, and labor-intensive construction method. This research conducted by Descriptive-Analytics and Comparative methods. Descriptive-Analytics to reveal the innovation of which parts of Kayu Gelam could be explored into architectural faÃ§ade, so itâ€™s applicable to Low-Waged House without made it â€˜cheapâ€™. While Comparative method used to compare all aspects in it, like technique, price, and its contribution in digging Local Wise potential up in modern constellation.